The perfect meal : the multisensory science of food and dining - Spence, Charles; Piqueras-Fiszman, Betina (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2014)
"The authors of The Perfect Meal examine all of the elements that contribute to the diner's experience of a meal (primarily at a restaurant) and investigate how each of the diner's senses contributes to their overall multisensory experience. The principal focus of the book is not on flavor perception, but on all of the non-food and beverage factors that have been shown to influence the diner's overall experience. Examples are: the colour of the plate (visual) the shape of the glass (visual/tactile) the names used to describe the dishes (cognitive) the background music playing inside the restaurant (aural)Novel approaches to understanding the diner's experience in the restaurant setting are explored from the perspectives of decision neuroscience, marketing, design, and psychology"--
"The first book dedicated to the sensory science behind "eating out", considering every sensation involved in the dining experience"--
' -- 2.3.2. 'This dessert is literally calling me' -- 2.3.3. Images on the menu -- 2.3.4. On a diet? Does nutritional information help? -- 2.3.5. Price and behaviour -- 2.3.6. On the format of the menu -- 2.4. Conclusions -- -- 3. Tastes Great, But What do We Call It? The Art and Science of Food Description -- 3.1. Introduction -- 3.2. Snail porridge -- 3.3. Can labelling enhance the taste and/or flavour of food? -- 3.4. Interim summary -- 3.5. On the neuroscience of naming food -- 3.6. Naming names -- 3.7. Does food labelling influence the perceived ethnicity of a dish? -- 3.8. Natural and organic labels -- 3.9. Health/ingredient labels -- 3.10. Local labels -- 3.11. Descriptive food labelling -- 3.12. Labelling culinary techniques -- 3.13. Surprise! -- 3.14. Expectations and reactions -- 3.15. Conclusions -- -- 4. Plating and Plateware: On the Multisensory Presentation of Food -- 4.1. Introduction -- 4.2. A potted history of food presentation -- 4.3. The plate: the essential element of our everyday meal -- 4.3.1. On the colour of the plate -- 4.3.2. The shape of the plate -- 4.3.3. The size of the plate -- 4.3.4. On the haptic aspects of the plateware -- 4.4. Interim summary -- 4.5. The plate that is not a plate -- 4.5.1. Reaching new heights -- 4.5.2. On the smell and sound of the plateware -- 4.5.3. Camouflage -- 4.5.4. Improvised plateware -- 4.5.5. Purpose-made plateware -- 4.6. On the multiple contributions of the visual appearance of a dish -- 4.6.1. On the importance of harmony on the plate -- 4.7. Individual diner responses to the visual presentation of food -- 4.8. Conclusions -- -- 5. Getting Your Hands on the Food: Cutlery -- 5.1. Introduction -- 5.2. The story of cutlery -- 5.3. The material qualities of the cutlery -- 5.3.1. The quality of the cutlery -- 5.3.2. Tasting the cutlery -- 5.4. Size matters -- 5.5. On the texture/feel of the cutlery -- 5.6. Colourful cutlery -- 5.7. Cutlery that is not -- 5.8. Finger food -- 5.9. Eating without hands -- 5.10. Conclusions -- -- 6. The Multisensory Perception of Flavour -- 6.1. Introduction -- 6.2. Perceiving flavours -- 6.3. Taste -- 6.3.1. Are you a supertaster? -- 6.4. Olfactory-gustatory interactions -- 6.4.1. Cross-cultural differences in multisensory flavour perception -- 6.5. Oral-somatosensory contributions to multisensory flavour perception -- 6.5.1. Are you a thermal taster? -- 6.6. Interim summary -- 6.7. The sound of food -- 6.8. Visual flavour -- 6.8.1. How does colour influence flavour perception? -- 6.8.2. Summary of research on visual flavour -- 6.9. The cognitive neuroscience of multisensory flavour perception -- 6.10. Conclusions -- -- 7. Using Surprise and Sensory Incongruity in a Meal -- 7.1. Introduction -- 7.2. How did sensory incongruity become so popular and why is it so exciting? -- 7.2.1. The search for novelty -- 7.2.2. The rise of molecular gastronomy/modernist cuisine -- 7.2.3. The rise of sensory marketing and multisensory design -- 7.2.4. Globalization -- 7.3. Defining sensory incongruity -- 7.4. Noticing sensory incongruity -- 7.4.1. Disconfirmed expectations -- 7.4.2. Hidden and visible incongruity -- 7.5. A brief history of sensory incongruity at the dinner table -- 7.6. Colour-flavour incongruity -- 7.7. Format-flavour incongruity -- 7.8. Smell-flavour incongruity -- 7.9. Interim summary -- 7.10. The diner's response to sensory incongruity -- 7.10.1. Attentional capture -- 7.10.2. Surprise -- 7.10.3. Memorability -- 7.11. Molecular gastronomy and surprise -- 7.12. Sensory incongruity and the concept of `naturalness' -- 7.13. Individual differences in the response of diners to sensory incongruity -- 7.14. Conclusions -- -- 8. Looking for Your Perfect Meal in the Dark -- 8.1. Introduction -- 8.2. The social aspects of dining in the dark -- 8.3. Why are dining in the dark restaurants so popular nowadays? -- 8.4. Seeing or not seeing (correctly) the food -- 8.4.1. The importance of colour to food -- 8.4.2. Do our other senses really become more acute in the dark? -- 8.5. Does dining in the dark really capture how the blind experience food? -- 8.6. Cooking in the dark -- 8.7. Conclusions -- -- 9. How Important is Atmosphere to the Perfect Meal? -- 9.1. Introduction -- 9.2. Atmospherics and the experience economy -- 9.3. The Provencal Rose paradox -- 9.4. Does the atmosphere really influence our appraisal of the meal? -- 9.5. On the ethnicity of the meal -- 9.6. Tuning up how much money and time we spend at the restaurant -- 9.6.1. The style and volume of the music -- 9.6.2. The tempo of the music -- 9.6.3. "Pardon?'' -- 9.7. Context and expectation -- 9.8. The lighting -- 9.9. The olfactory atmosphere -- 9.10. On the feel of the restaurant -- 9.11. Atmospheric contributions to taste and flavour perception -- 9.12. Multisensory atmospherics -- 9.13. Conclusions -- -- 10. Technology at the Dining Table -- 10.1. Introduction -- 10.2. Technology on the dining table -- 10.3. Transforming the dining experience by means of technology -- 10.4. Augmented Reality (AR) food: A case of technology for technology's sake? -- 10.5. Using QR codes to change our interaction with food -- 10.6. Fostering healthy eating through the incorporation of technology -- 10.7. Technology and distraction -- 10.8. Using technology to control the multisensory atmosphere -- 10.9. On the neuroscience of matching sound to food (and how technology might help) -- 10.10. On the future of technology at the table: digital artefacts -- 10.11. The SmartPlate -- 10.12. Anyone for a 'Gin & Sonic'? -- 10.13. The tablet as twenty-first century plateware? -- 10.14. Tips from the chef at the tips of your fingers -- 10.15. Conclusions -- -- 11. On the Future of the Perfect Meal -- 11.1. Introduction -- 11.2. On the history of predicting the future of food -- 11.2.1. A meal (or even a day's food) in a single dose -- 11.2.2. On the mechanization of feeding -- 11.2.3. Air 'food' -- 11.2.4. Artificial flavours -- 11.3. From the past to the future of food -- 11.3.1. Sous vide as the twenty-first century microwave -- 11.3.2. 3D printed food: an astronomical idea -- 11.3.3. On the future of cultured meat -- 11.3.4. Note-by-note cuisine -- 11.3.5. Eating insects for pleasure: bug burger with insect paste, anyone? -- 11.3.6. The new algal cuisine -- 11.4. Anyone for a spot of neo-Futurist cuisine? -- 11.4.1. Food theatre: food as entertainment -- 11.4.2. Plating art -- 11.5. Interim summary -- 11.6. Acknowledging our differences -- 11.7. The meal as catalyst for social exchange -- 11.8. Is it a restaurant or is it a science laboratory? -- 11.9. Pop-up dining, story telling and the joys of situated eating -- 11.10. Conclusions.
Includes index.
Machine generated contents note: Introducing the perfect meal Let the show commence: On the start of the perfect meal Tastes great, but what do we call it? The art and science of food description Plating and plateware: On the multisensory presentation of food Getting your hands on the food: Cutlery The multisensory perception of flavour Using surprise and sensory incongruity in a meal Looking for your perfect meal in the dark How important is atmosphere to the perfect meal? Technology at the dining table On the future of the perfect meal.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Gastronomy; Dinners and dining; Food -- Sensory evaluation; Senses and sensation; Intersensory effects; TECHNOLOGY & ENGINEERING -- Food Science; Dinners and dining; Food -- Sensory evaluation; Gastronomy; Intersensory effects; Senses and sensation; Electronic books